The complex relationship between climate anomalies and reproductive attitudes and practices in low- and middle-income countries - Brown, Meg L.; Severson, Alex; Tiedt, Sonia; Beeman, Aly; Fuchs, Nomi R.; Gibbs, Theodora (Frontiers in Global Women's Health, 2025)
IntroductionClimate change significantly impacts sexual and reproductive health (SRH) attitudes and practices, yet large-scale quantitative analyses exploring these effects are limited. This study investigates the historical associations between climate change, specifically temperature and precipitation anomalies, and key SRH attitudes and practices including contraception use, fertility preferences, and contraceptive autonomy.MethodsUsing data from 74 IMPUMS-harmonized Demographic and Health Surveys merged with high-resolution climate data, we analyzed a sample of 820,746 non-pregnant, reproductive-aged women across 33 low- and middle-income countries from 2000 to 2016. Fixed-effect logistic regression models were employed to assess the association between climate anomalies and SRH attitudes and practices.ResultsPooled sample results indicate modest but significant associations globally: higher exposure to extreme heat in the year prior to survey administration was associated with lower odds of modern contraception use, lower odds of desire for children, and higher odds of contraceptive autonomy, while higher exposure to extreme precipitation was associated with lower odds of desire for children and higher odds of contraceptive autonomy. These associations were more pronounced when both temperature and precipitation anomalies occurred concurrently. Substantial demographic and geographic variability were observed, with mixed directionality and strength of association observed across countries and stronger associations observed among nulliparous women and younger respondents.DiscussionOur findings underscore the potential impact of climate change on SRH attitudes and practices, as well as SRH service delivery needs in the context of extreme heat and extreme precipitation, highlighting the importance of targeted, gender-responsive health interventions tailored to climate change-affected populations.